Avaliaç\~ao dos condicionantes de abandono contratual e viabilidade econômica da relicitaç\~ao em concess\~oes de infraestrutura pela abordagem das opç\~oes reais - Felipe Amaral Costa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The objective of the study is to present a model, based on the application of the Theory of Real Options (TRO), for the regulatory improvement of the methodology for calculating restitutions related to investments in reversible assets in the event of early termination of road concessions through devolution friendly (Law No. 13,448/2017), seeking to reach its "fair value". To this end, a series of sensitivity analyzes were carried out for those variables that exert the greatest influence on the behavior of the option. In addition, its dynamics in different contractual arrangements, auction modalities and methods of quantification of indemnity and pricing of options were evaluated. By means of the sensitivity analysis, increasing the reimbursable figures, an upward trend in the value of the option, in the probability of exercise and in the necessary contingency for the indemnity funds was evidenced. Encouraging the adoption of hyper-aggressive strategies by bidders is also a possible adverse consequence that can be had with the flexibility of hypotheses for the termination of contracts, if they are assured of a guarantee of return on part of the investments made. The work demonstrated that the abandonment option is significantly affected by the discount applied to the auction's base rate: the greater the discount, the more valuable the option becomes and the more certain is the premature termination of the contract.
Keywords: 330; infrastructure concessions; rebidding; real options